"This will help in healing our land": Remembering and forgetting Quatro in post-apartheid South Africa - Kaden, Robert (Faculty of Humanities, University of the Free State, 2012)
This article employs the history of Umkhonto we Sizwe (MK)’s 1980s prison camp, Quatro, as a case study to broadly explore the political jockeying over the memory of anti-apartheid prison camps (as sites of human rights abuses) in the context of post-apartheid South Africa. This is done by tracing how the collective memory of Quatro had been received and interpreted by different political groups and the media in post-apartheid South Africa. This article proposes that, with regard to the collective memory of Quatro, two diverging streams of memory politics co-exist in post-apartheid South Africa: one that chooses to remember, and one that chooses to forget. Both these streams reinforce the “Rainbow Nation” mentalité or the myth of the “new South Africa”, albeit in different ways. Opposition groups like the former National Party (NP) and the Democratic Alliance (DA) have frequently drawn on the collective memory of Quatro as a way of challenging the ruling African National Congress (ANC)’s hegemonic position. Much of this is framed in the context of the democratic rhetoric of post-apartheid South Africa. The ruling ANC, on the other hand, has negated the ambiguous narrative and traumatic memory of Quatro in order to write a “shared history” of the past that can foster a “new South Africa”.
Keywords: African National Congress (ANC); Angola; Democratic Alliance (DA); L’histoire de mentalities; Memory; Post-apartheid South Africa; Quatro; Rainbow nation; Trauma; Truth and Reconciliation Commission (TRC); Umkhonto we Sizwe (MK)